Comparison between platelet rich plasma injection, corticosteroid injection and short-wave diathermy in the management of pain and the improvement of functional outcome in the patients suffering from adhesive capsulitis of the shoulder: a randomized controlled trial - Deb, Debasish; Nandabir, Yumnam Singh; Singh, Naorem Bimol; Das, Rakesh; Meethal, Shanavas Anoth (International Journal of Advances in Medicine, 2020)
Background: Adhesive capsulitis of shoulder is characterized by pain and restricted range of motion and has a wide variety of treatment options without any substantial evidence. Platelet rich plasma (PRP) is one of the newer treatment modalities and its efficacy needs to be compared with other routine treatment modalities. Method: A randomized controlled trial was conducted in the Department of Physical Medicine and Rehabilitation, Regional Institute of Medical Sciences (RIMS), Imphal for a period of 1-year February 2019 to January 2020. One hundred ninety-five patients with adhesive capsulitis recruited and randomized, patients received single PRP injection (2 ml) or corticosteroid (80 mg methyl prednisolone) or shortwave diathermy (10 settings continuous mode using 27.12 MHz). Results: The primary outcome measure was active range of motion of the shoulder and the secondary outcome measures included Visual analogue scale (VAS) for pain and a shortened version of Disabilities of the Arm, Shoulder and Hand (Quick DASH) for function. Patients were evaluated at 0, 3, 6 and 12 weeks. Chi-square test and ANOVA were used to determine significant differences. PRP treatment resulted in statistically significant improvement over corticosteroid at 12 weeks and over short-wave diathermy therapy at 6 weeks. Conclusion: This study demonstrates that single injection of PRP is more effective than corticosteroid or short-wave diathermy in the treatment of adhesive capsulitis of shoulder.